Platelet Shape Change Evoked by Selective Activation of P2X1 Purinoceptors with α,β-Methylene ATP - Rolf, Michael G.; Brearley, Charles A.; Mahaut-Smith, Martyn P. (Thrombosis and Haemostasis, 2001)
Simultaneous measurements of [Ca2+]i and light transmission were used to examine the relationship between P2X1 receptor activation and functional platelet responses. The P2X1 agonist α,β-MeATP evoked a transient [Ca2+]i increase and a reversible decrease in light transmission; both responses required external Ca2+ and the nucleotidase apyrase. The transmission response was due to shape change only, verified by scanning electron microscopy and insensitivity to Reopro, a GPIIbIIIa antagonist. α,β-MeATP stimulated smaller shape changes than ADP, however P2X1 responses had a lifespan of <2 h following resuspension in saline and may be considerably larger in vivo. A peak [Ca2+]i increase of >50 nM was required for detectable shape change. Overlap of concentration-response relationships for α,β-MeATP-evoked [Ca2+]i and shape change suggests that other second messengers are not involved. Therefore, the physiological P2X1 agonist ATP can contribute to platelet activation, in contrast to its previously described inhibitory action at metabotropic platelet purinoceptors.
Keywords: Platelets; P2X receptors; ATP; purinoceptors; shape change